2022
DOI: 10.1590/1981-6723.00222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intrinsic and extrinsic factors on the sensory perception and intention to purchase buffalo meat by consumers in Southeast Brazil

Abstract: This study aimed to evaluate the effect of extrinsic factors (meat type, price, and nutritional claims) on purchase intention and the perception of intrinsic factors (tenderness, juiciness and flavor) in buffalo loin in a region of Brazil where the marketing of buffalo meat is not common. Photos of the steaks were treated and labels were designed to simulate the retail purchase process, with the effects of extrinsic factors being evaluated through conjoint analysis. Sensory tests of difference from control, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For instance, a study on the sensory perception of processed orange juice found that the acceptance of processed juices was higher when consumers were informed about the juice's processing characteristics, ingredients, durability, and price [8]. Similarly, research on buffalo meat in Southeast Brazil revealed that price and nutritional information significantly influenced consumer's sensory perception and purchase intention [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, a study on the sensory perception of processed orange juice found that the acceptance of processed juices was higher when consumers were informed about the juice's processing characteristics, ingredients, durability, and price [8]. Similarly, research on buffalo meat in Southeast Brazil revealed that price and nutritional information significantly influenced consumer's sensory perception and purchase intention [9].…”
Section: Literature Reviewmentioning
confidence: 99%